The Urgency of Implementing Exhausion of Local Remedies In Investment Dispute Settlement Regarding Mining Licenses In Indonesia - Adiza, Salza Fadila; Amalia, Prita; Agusman, Damos Dumoli (Journal of Law and Policy Transformation, 2024)
The exhaustion of local remedies (ELR) is a principle viewed as an exception rather than a rule in international investment law. Hence, it tends to be forgotten, and Investor-State Dispute Settlement (ISDS) is preferable in resolving disputes concerning mining licenses. However, this has proven detrimental to Indonesia as a developing country. This research aims to analyze ELR implementation in international investment law and the urgency of implementing ELR for Indonesia as a developing country. This research uses normative and comparative juridical methods to find that ELR remains an important principle despite being generally waived and that there is an urgency for Indonesia as a developing country to implement ELR to (1) reassert sovereignty; (2) minimize financial loss; (3) improve domestic adjudication and strengthen rule of law. Implementing ELR can be done through BITs by referring to India and Argentina as models. An amendment to domestic law and regulation is also needed to ensure the enforceability of ELR in Indonesia.